2011
DOI: 10.56702/uckx8598/jcrp0201.7
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Overlap of School Counselor Identity and Duties

Abstract: Professional school counselors (N=92) across grade levels completed the Professional Identity of School Counselors survey (PISC) online to provide their views of professional identity and the concepts of leadership, collaboration, advocacy, multiculturalism, and the general delivery (e.g., counseling, consulting, individual planning, and guidance curriculum), management (i.e., how school counselors organize their time in meeting student needs), and accountability (e.g., collecting, using, and reporting the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There are also additional challenges for school counselors and school psychologists in rural schools, particularly related to establishing connections and collaborations. In general, school counselors report that collaboration with other school professionals is relatively frequent and includes various stakeholders, including school psychologists (Gibbons, Diambra, & Buchanan, 2010); however, these collaborations were not defined as an "easy or smooth task" (p. 19). In particular, collaboration is difficult in schools where distance and schedules limit or prevent interaction.…”
Section: Ssp Collaboration With Rural Educatorsmentioning
confidence: 99%
“…There are also additional challenges for school counselors and school psychologists in rural schools, particularly related to establishing connections and collaborations. In general, school counselors report that collaboration with other school professionals is relatively frequent and includes various stakeholders, including school psychologists (Gibbons, Diambra, & Buchanan, 2010); however, these collaborations were not defined as an "easy or smooth task" (p. 19). In particular, collaboration is difficult in schools where distance and schedules limit or prevent interaction.…”
Section: Ssp Collaboration With Rural Educatorsmentioning
confidence: 99%
“…Collaboration within educational contexts has been described as an action-focused process that can help solve challenges that schools face (Hargreaves, 1994). Gibbons et al (2010) identified an essential feature of collaboration as "recognition that all stakeholders have a unique knowledge base and perspective equal in value and importance to the process" (p. 338). The knowledge and perspectives that school counselors and teachers have regarding their multilingual learner students can be best utilized when shared so that counselors and teachers can make decisions based on student needs and identities.…”
Section: School Counselor and Teacher Collaborationmentioning
confidence: 99%